Medication errors in paediatric outpatients. Issue 6 (10th August 2010) - Kaushal, Rainu; Goldmann, Donald A; Keohane, Carol A; Abramson, Erika L; Woolf, Seth; Yoon, Catherine; Zigmont, Katherine; Bates, David W
Abstract : Background: Medication errors are common in many settings and have important ramifications. Although there is growing research on rates and characteristics of medication errors in adult ambulatory settings, less is known about the paediatric ambulatory setting. Objective: To assess medication error rates in paediatric patients in ambulatory settings. Methods: The authors conducted a prospective cohort study of paediatric patients in six outpatient offices in Massachusetts. Data were collected using duplicate prescription review, two parental surveys and chart review. A research nurse classified all medication errors by stage and type of error. Results: The authors identified 1205 medication errors with minimal potential for harm (rate: 68% of patients, 95% CI 64 to 72%; 53% of Rx, 95% CI 50 to 56%) and 464 potentially harmful medication errors (ie, near misses) (rate: 26% of patients, 95% CI 24 to 28%; 21% of Rx, 95% CI 19 to 22%). Overall, 94% of the medication errors with minimal potential for harm and 60% of the near misses occurred at the prescribing stage. The most common types of errors were inappropriate abbreviations followed by dosing errors. The most frequent cause of errors was illegibility. Conclusion: With paper prescribing, half the prescriptions had medication errors, and one in five had a potentially harmful error. These rates are very high. Interventions targeting the ordering and administration stages have the greatest potential benefit.